2018
DOI: 10.29052/ijehsr.v6.i1.2018.39-46
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Physical Restraint Use in Critically Ill Patients

Abstract: Background: Patients in critical care setting often encounter severe delirium and agitation putting them at risk of harm. So it has become a common trend to restraint patient physically in intensive care units. However, physical restraint has several adverse physical, psychological and ethical consequences. Awareness regarding significant risk associated with physical restraint, continuing education and skills stabilize the patient's safety and potential complication regarding ethical and legal issues to physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The current study reported that; existence of improvement in stroke severity among study group than control group at third and fourth measurements by proper application of care pathway; this result supported by [21] they documented that; proper identification of stroke severity is an indicator for appropriate planned care by neurologists and neuroscience nurses, wherever they observing and changes in the patient's neurological status and measuring stroke severity for early recovery and improving from stroke. On the other hand the improvement in stroke severity among study group occurred by the effect application clinical pathway which included performing of coma arousal technique; this result supported by [22] and [23] they reported that; proper nursing care and application of coma arousal technique decreased occurrence of physiological parameters adverse events by. The researcher explained that; the stroke severity among study group decreased by application of planned care and closed follow up via clinical pathway team.…”
Section: As Regards To Demographic Characteristics and Medical Datamentioning
confidence: 51%
“…The current study reported that; existence of improvement in stroke severity among study group than control group at third and fourth measurements by proper application of care pathway; this result supported by [21] they documented that; proper identification of stroke severity is an indicator for appropriate planned care by neurologists and neuroscience nurses, wherever they observing and changes in the patient's neurological status and measuring stroke severity for early recovery and improving from stroke. On the other hand the improvement in stroke severity among study group occurred by the effect application clinical pathway which included performing of coma arousal technique; this result supported by [22] and [23] they reported that; proper nursing care and application of coma arousal technique decreased occurrence of physiological parameters adverse events by. The researcher explained that; the stroke severity among study group decreased by application of planned care and closed follow up via clinical pathway team.…”
Section: As Regards To Demographic Characteristics and Medical Datamentioning
confidence: 51%
“…The negative effect of older age and other associated factors, including diagnosis at admission, comorbidities and functional status, has been recognized in numerous studies [2][3][4][5][6][7] . Hence, these factors together are better at predicting ICU outcomes than the age alone 8,9,10 . The instruments used are sophisticated, but still, the morbidity and mortality rates are very high.…”
Section: Introductionmentioning
confidence: 98%
“…Clinical justification to use PR in intensive care units is to support ongoing treatment such as accessing invasive medical devices and to avoid unplanned treatment intrusion (Duwadi, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Without a doubt, the use of restraint techniques in ICUs is for the protection of the patients, reducing the possibility of intentional as well as unintentional removal of medical equipment. Help the patient who refuses to cooperate with bedside procedures as well (Duwadi, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%